Emerging priorities in terrestrial herbivory research in the Arctic - Isabel C. Barrio; Katariina E.M. Vuorinen; Laura Barbero-Palacios; Mathilde Defourneaux; Matteo Petit Bon; Eleanor A. Greer; Helen B. Anderson; Tim Horstkotte; Nicolas Lecomte; Torben Windirsch; Kristy Ferraro; Bruce C. Forbes; et al. (Arctic Science)
Herbivores are an integral part of Arctic terrestrial ecosystems, driving ecosystem functioning and sustaining local livelihoods. In the context of accelerated climate warming and land use changes, understanding how herbivores contribute to the resilience of Arctic socio-ecological systems is essential to guide sound decision-making and mitigation strategies. While research on Arctic herbivory has a long tradition, recent literature syntheses highlight important geographical, taxonomic, and environmental knowledge gaps on the impacts of herbivores across the region. At the same time, climate change and limited resources impose an urgent need to prioritize research and management efforts. We conducted a horizon scan within the Arctic herbivory research community to identify emerging scientific and management priorities for the next decade. From 288 responses received from 85 participants in two online surveys and an in-person workshop, we identified 8 scientific and 8 management priorities centred on (a) understanding and integrating fundamental ecological processes across multiple scales from individual herbivore–plant interactions up to regional and decadal scale vegetation and animal population effects; (b) evaluating climate change feedbacks; and (c) developing new research methods. Our analysis provides a strategic framework for broad, inclusive, interdisciplinary collaborations to optimise terrestrial herbivory research and sustainable management practices in a rapidly changing Arctic.